Organizational Culture with Transformational Leadership Style on Production Supervision at PT Diamondfit Garment Indonesia - umi supriyati; sutarto wijono (Universitas Pendidikan Ganesha, 2021)
The success of an organization is largely determined by the quality of the people who work in it. In developing an organization, a leader is needed who is able to become a driving force in encouraging employees to have high motivation to be able to increase employee performance productivity. With the transformational leadership style, it can inspire and motivate employees to improve their performance optimally so that organizational goals can be achieved as much as possible without any pressure or coercion from the leader. The concept of transformational leadership integrates ideas developed in a character, style and contingency approach. This research was conducted with the aim of knowing the relationship between organizational culture and transformational leadership style in all production supervisors at PT. Diamondfit Garment Indonesia. In this study using quantitative research methods with a sample of 30 employees with production supervisor positions at PT. Diamondfit Garment Indonesia, then data analysis was performed using Pearson Momemt Product from SPSS Statistics version 21.0 for Windows. From the research that has been done, it shows the results (r = 0.461) and the correlation significantly shows the value of sig. p=0.005 (p<0.05) with a positive correlation coefficient, it can be concluded that there is a significant positive relationship between organizational culture and transformational leadership style.